Banking Sector Reforms in India: Review, Problem and Prospect - Ms. Shinki K Pandey, Ms. Neha Choithramani (Mathematical Statistician and Engineering Applications, 2022)
The Indian financial system has experienced remarkable successes during the last 30 years. It is no longer limited to cosmopolitans and metropolitans. In reality, India's financial system has now reached even the most distant parts of the country. Since the whole process of banking reform and deregulation began in 1991, India's banking industry has seen significant upheaval. The primary goal of this reform is to make India's banking industry competitive, lucrative, and productive. Banks in India, particularly public sector banks and historic private banks, are unable to compete. With one exception, they are unable to equal profitability and productivity.